The structure of intellect: The comparison of WISC profiles of mentally retarded and learning-disabled children - Pukinskaitė, R. (Psichologija, 1996)
The present paper reveals the peculiarities of the structure of the intellect of mentally retarded pupils, learning-disabled pupils, and pupils with high achievements. The experimental investigation has shown a significant difference between all the groups in the WISC results of full-scaled scores, verbal and performance scores (p<0,05). The performance IQs of children with leaming disabilities were significantly higher than their verbal IQs. The profile of children with auditory - visual disorders has a tendency to become flatter (there is no significant difference between verbal IQs and performance IQs). The largest variability of WISC scaled scores appeared in the results of children with high achievements, and the smallest variability, in the results of mentally retarded children.